A comprehensive review on consumption of Bushmeat in humans and effects on wildlife (Zoo Botanica, 2025)
The term “Bushmeat” means harvesting the meat of wild animals or game animals for the purpose of consumption and meeting the dietary requirements of local inhabitants of the African continent. Harvesting of wild animal meat is done not only for the purpose of consumption but also for ensuring Food security, Income and for the Trading. “Bushmeat” is a fundamental wellspring of protein in numerous provincial regions and diminished accessibility can have negative effects on well-being just as nourishment impacts. Guaranteeing the maintainability of bushmeat utilization is significant for both biodiversity protection and destitution mitigation in tropical creating nations, yet we think minimal about the job of chasing and bushmeat utilization in the everyday lives of provincial networks. In Africa, over hunting of tropical untamed life for sustenance stays an obstinate subject. Givers and governments stay resolved to spend in endeavors to both ration and permit the feasible utilization of untamed life. Four head obstructions should be survived.People groups are not propelled to save natural life-long haul since they have no formal rights to profit by untamed life, or to avoid others from taking it on their property. Multi species harvests, run of the mill of bushmeat chasing situation, place enormous bodied species in danger of elimination. Natural life generation can't extend, similarly that animals cultivating can, to meet the normal development in buyer request. Untamed life living space is lost through change to horticulture, lodging, transportation systems and extractive enterprises. In this review, we look at the on-screen characters associated with the utilization of natural life as nourishment and contend the potential arrangements required to address urban and rustic bushmeat utilization.
Keywords: Africa; bushmeat; consumption; wildlife; zoonotic diseases